The basics of requirements analysis in the methodology of ECM systems implementation - Wójtowicz, Radosław (Podstawy analizy wymagań w metodyce implementacji systemów ECM, 2019)
The article presents the basics of requirements analysis with respect to the general concept and methodology of implementing content management systems in organisations. The essential aim of the article is to present selected aspects of the concept of requirements analysis applied in the case of Enterprise Content Management (ECM) class systems. The literature on applications of IT systems still lacks a systemic approach to the implementation of ECM class systems, and above all, a presentation of the vital role of requirements analysis at the pre-implementation stage. Therefore, this article is an attempt to fill this gap. The first part of the article will present the most important concepts related to the area described. The main content of the article is the second part, which contains a description of the proposed approach to requirements analysis, supported by relevant examples
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 88-99
Keywords: informatyka ekonomiczna